Finding a “way out”: deferring treatment decisions as a strategy for closing medical consultations in China - Lu Liu; Wen Ma (Humanities & Social Sciences Communications)
Abstract This article explores participants’ agreement to defer treatment decisions during doctor–patient negotiations of surgical treatment recommendations in China. As a recurrent outcome of medical consultations in Chinese clinical contexts, deferring treatment decisions is often used by both doctors and patients as a strategy to close the consultation when the two parties are at an impasse due to conflicting treatment preferences. It is not uncommon for clear decisions about surgical treatments to remain unresolved within the limited time of a consultation, particularly when doctors view surgery as the ultimate or even the only effective treatment, while patients consistently resist it. These treatment negotiations often reach a deadlock, with neither party willing to concede. When no agreement is reached, the consultation cannot be closed. In such cases, participants may propose deferring the treatment decision. This proposal can be initiated by either patients, through inquiries or statements, or by doctors, through inquiries or directives. Once an agreement to defer the decision is reached, the consultation can proceed toward closure. This study aims to introduce an alternative outcome to the typical “here-and-now” decisions (acceptance or rejection): the agreement to defer treatment decisions. We argue that this outcome emerges from the interplay between doctors’ and patients’ rights during the negotiation of surgical treatment recommendations. It reflects a balanced, yet delicate, relationship between doctors and patients. Using conversation analysis (CA) methodology and data drawn from authentic clinical consultations, we analyze in detail the specific practices that lead to this outcome.